Analisis Sektor Unggulan: Studi Kasus Wilayah Metropolitan Menado - Elprida Sigiro, Ely; Anugerah, Yoseph (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2022)
North Sulawesi is one of the provinces that the government will pay more attention to because it includes areas that will become new metropolitan areas, namely the Manado Metropolitan Area, which consists of 3 related cities/regencies Manado City, Bitung City, and North Minahasa Regency. The need to know the potential possessed by the Manado Metropolitan Region through a leading sector approach. The analytical tool used is the location quotient to find out the leading sector and the dynamic location quotient to find out the potential of the leading sector. The data used is GRDP at constant prices and the growth rate of North Sulawesi Province in 2014-2018. The calculation results show the variety and potential leading sectors among the cities.